PERANAN BARISTA DALAM MENYAJIKAN MINUMAN KOPI BERKUALITAS DI CAFE EXCELSO VITKA POINT TIBAN KOTA BATAM - Abd. Rahman Yusuf; Syafruddin Rais (Puslitabmas Batam Tourism Polytecnic, 2023)
The role of baristas are as someone who brews and serves espresso based coffees. Espresso is a type of coffee made from the extraction of grounded coffee beans added with hot water under high pressure. This research aimed to find out about the role of baristas in serving high quality coffee at Excelso Cafe Vitka Point Tiban Batam. The theories used in this research were the theories of the baristas' role, and high quality coffee. This research used the quantitative approach with descriptive approach. There were 3 phases of data collection, which was observation, interview and documentation, which was then analyzed through 4 phases of data analyzing, starting with data collecting, data reduction, data serving and conclusion.